Beyond the pulse: unusual presentations of Takayasu’s arteritis - Sharma, Pallav K.; Kumar, Chandan; Kumar, Suraj (International Journal of Research in Medical Sciences, 2024)
Takayasu’s arteritis (TA) a.k.a pulseless disease is a chronic inflammatory occlusive thrombo-aortopathy. It is a rare inflammatory disease affecting large arteries, often leading to significant diagnostic challenges, especially when presenting with atypical symptoms. This case report explores a patient, whose primary complaints were chest pain and no neurological or constitutional symptoms, diverging from the common presentations of diminished pulses or limb claudication. Advanced imaging, including CT Aortogram and interventions like cardiac angiography, played a crucial role in detecting vascular inflammation and stenosis, facilitating accurate diagnosis and management. The case underscores the importance of considering Takayasu arteritis in differential diagnoses, even with non-classical presentations. This present case demonstrates rare and unique presentation of TA where patient presents with myocardial infarction and cardiogenic shock and also explains the diagnostic dilemma of TA with such unusual presentation.